2020
DOI: 10.2139/ssrn.3526809
|View full text |Cite
|
Sign up to set email alerts
|

Other-Regarding Preferences and Redistributive Politics

Abstract: Increasing inequality and associated egalitarian sentiments have again put redistribution on the political agenda. Support for redistribution may also be affected by altruistic and egalitarian preferences, but knowledge about the distribution of these preferences in the broader population and how they relate to political support for redistributive policies is still scarce. In this paper, we take advantage of Swiss direct democracy, where people voted several times in national plebiscites on strongly redistribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…2 Examples include redistribution (Fisman, Jakiela and Kariv, 2017;Almås, Cappelen and Tungodden, 2020;Epper, Fehr and Senn, 2020) and public goods production (Fehr and Gächter, 2002;Rand et al, 2009;Hauser et al, 2014;Lergetporer et al, 2014;Gächter, Kölle and Quercia, 2017;Molleman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2 Examples include redistribution (Fisman, Jakiela and Kariv, 2017;Almås, Cappelen and Tungodden, 2020;Epper, Fehr and Senn, 2020) and public goods production (Fehr and Gächter, 2002;Rand et al, 2009;Hauser et al, 2014;Lergetporer et al, 2014;Gächter, Kölle and Quercia, 2017;Molleman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cohn et al (2019). In a recent study in Switzerland, laboratory behavior has been shown to predict individuals' support for redistributive policies in national plebiscites (Epper et al 2020).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Other differences in the evolution of incomes can be observed in the U.S., e.g., between college educated and non-college educated (Goldin and Katz, 2007), between men and women (Blau and Kahn, 2017), and between Caucasians and African-Americans (Bayer and Charles, 2018). 2 Fisman et al (2017), Kerschbamer and Müller (2020), Epper et al (2020), and Almås et al (2020) show that elicited social preferences correlate with political support for redistributive policies at the societal level.…”
Section: Introductionmentioning
confidence: 99%